A&T Gujarat Implementation Research Baseline Survey 2022: Frontline Workers - International Food Policy Research Institute (International Food Policy Research Institute, 2025)
This dataset originates from the Frontline Workers (FLW) Survey, conducted as part of the baseline for the impact evaluation of the Alive & Thrive (A&T) project in Gujarat, India. The study assessed the effectiveness of systems-strengthening interventions and local governance engagement in improving the quality and co-coverage of health and nutrition services in Gujarat, India.